About the Ricci flow on three-dimensional non-unimodular Lie groups with semisymmetric equiaffine connection - Grigoryev, Danila S.; Oskorbin, Dmitrii N.; Rodionov, Eugene D. (Journal of the Belarusian State University. Mathematics and Informatics, 2025)
The Ricci flow on three-dimensional non-unimodular Lie groups with semisymmetric equiaffine connection is studied. The Ricci flow equation in the coordinate system proposed by J. Milnor is reduced to systems of algebraic and differential equations. A solution to the Ricci flow equation in the class of left-invariant Milnor metrics is found. The results of works by K. Onda, D. Knopf and K. McLeod concerning the Ricci flow on three-dimensional Lie groups in the case of Levi-Civita connectivity are generalised.